Doubling Rice Productivity in Bangladesh: A Way to Achieving SDG 2 and Moving Forward - Kabir, M S; Salam, MU; Islam, AKMS; Sarkar, M A R; Mamun, MAA; Rahman, MC; Nessa, B; Kabir, MJ; Shozib, HB; Hossain, MB; et al. (Bangladesh Rice Journal, 2021)
Built on deep-rooted political and cultural heritage, ‘rice security’ is the foundation of ‘food security’ in Bangladesh. The country has been in production-surplus of rice in the current decade feeding over 165 million people. This on-going ‘selfsufficiency momentum’ would require to maintain to meet increased demand from growing future population. On developmental side, Bangladesh is placed among the three of the world’s fastest growing economies in the years through to 2050. Rice sector would need to match with the pace of this growth. In addition, agriculture sector, that includes rice, is to double the productivity as the government commits to meet the SDG goal 2.3.1. This study addresses those issues through scoping increased rice production and productivity in Bangladesh, developing a plan of work (POW) on translating the scope and designing implementation plans and actions, incorporating efficiency, resilience, stability and sustainability issues, to achieve the POW. The study has used brainstorming, and rigorous analysis to achieve the objectives. The productivity has been explained in terms of yield- and labour-productivity. The developed three-winged ‘doubling rice productivity (DRP)’ framework directs yield enhancement and production accumulation in unexplored spaces (Wing-1); increased adoption of mechanization to impact on labour productivity (Wing-2), and improvements in nutritional quality and rice-based product diversity, and stabilizing the farmgate price (Wing-3). Analyses show, from the baseline figure of 35.29 MT in 2015, rice production in the country can be raised to 46.90 MT in 2030, 54.09 MT in 2040 and 60.85 MT in 2050 with combined contributions of three pillars – yield improvements by enhanced varietal potential (Pillar 1), reduction in existing yield gap (Pillar 2) and production increase by exploring unexplored spaces for rice (Pillar 3) of Wing-1 of the DRP. This production will produce a surplus of 6.50, 10.29 and 13.65 MT in 2030, 2040 and 2050, respectively, over the production target (40.40, 43.80 and 47.20 MT in 2030 and 2050, respectively). Results further reveal that through scale-appropriate mechanization backed up by estimated fair price, labour productivity in rice will be doubled by 2029, meeting the SDG 2.3.1. Good number of released varieties have been identified to have specific nutritional trait, and value adding quality. We have emphasized on much needed actions on demand-driven research for varietal development and field-adoptable management, mechanization for transplanting and harvesting operations, accommodation of rice in unexplored spaces, farmer-based speedy seed multiplication and dissemination system, establishment of commission for agricultural costs and prices, input buffer stock terminals for managing production risk, long-term storage and export of surplus production, and research-publicity-market development for rice-based products through public-private partnership. It is concluded that efficiency, resilience and sustainability around the three wings of DRP in the rice production systems to be ensured to achieve the rice production, productivity and labour use estimates. Bangladesh Rice J. 24 (2): 1-47, 2021